The Influence of Market Orientation and Product Innovation on the Competitiveness of "Mie Jebew" MSMEs at the Situbondo Car-Free Day - Nindi Kamila Indawati; Dassucik; Ahmad Hafas Rasyidi (Danadyaksa: Post Modern Economy Journal, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are one of the key pillars of regional economies, as they play a significant role in creating employment opportunities, increasing community income, and promoting local economic growth. Competitiveness is a crucial factor in ensuring the sustainability of MSMEs amid increasingly intense market competition. This study aims to examine the influence of market orientation and product innovation on the competitiveness of Mie Jebew MSMEs at the Car Free Day (CFD) market in Situbondo. This research employed a quantitative approach using a survey method. The population consisted of 117 consumers, and the sample size was determined using the Slovin formula, resulting in 53 respondents selected from the population. The results of the t-test indicate that the calculated t-value for the market orientation variable was 3.907, which is greater than the t-table value of 2.000, while the product innovation variable obtained a calculated t-value of 2.189, also exceeding the t-table value of 2.000, with significance values (p < 0.05), indicating that both variables significantly affect competitiveness. The F-test results also demonstrate that market orientation (Sig. = 0.000 < 0.05) and product innovation (Sig. = 0.033 < 0.05) simultaneously have a positive and significant effect on competitiveness. Furthermore, the adjusted coefficient of determination (Adjusted R Square) was 0.467, indicating that 46.7% of the variance in competitiveness can be explained by market orientation and product innovation, while the remaining 53.3% is influenced by other factors not examined in this study.